Blockchain-enabled fog and edge computing : concepts, architectures, and applications - Rehan, Muhammad Maaz; Rehmani, Mubashir Husain, 1983- (Boca Raton, FL : CRC Press, 2021)
"This book is written for students, computer scientists, researchers and developers, who wish to work in the domain of blockchain and fog/edge computing. One of the unique features of this book is highlighting the issues, challenges, and future research directions associated with Blockchain-enabled fog and edge computing paradigm. We hope the readers will consider this book a valuable addition in the domain of Blockchain and fog/edge computing"--
OCLC-licensed vendor bibliographic record.
Keywords: Cloud computing; Blockchains (Databases); COMPUTERS / Networking / General; COMPUTERS / Programming / Software Development